Mama's coming home - Banks, Kate 1960-; Bogacki, Tomasz (New York Farrar Straus Giroux, 2003)
Papa prepares dinner and the boys set the table as they, the dog, and the cat eagerly await Mama's return home after work.
"Frances Foster books."
Keywords: Working mothers -- Fiction; Sex role -- Fiction; Family life -- Fiction